PEMANFAATAN ENGLISH MAGAZINE SEBAGAIMEDIA INOVATIF PEMBELAJARAN SPEAKINGSISWA VII MTs YAPI PAKEM SLEMAN YOGYAKARTA - Annida Nurul Faiza Asni, Yuli Purwaningsih, Rojaki (Pelita - Jurnal Penelitian Mahasiswa UNY, 2008)
This research is intended to increase English speaking ability in learningEnglish for the VII grade student of MTs YAPI Pakem Sleman Yogyakarta.The subject of this research is 42 VII grade students of M.Ts. YAPI PakemSleman Yogyakarta. This research is focused on the implementation of learningspeaking English through English magazine with two siclus, each of the siclusconsist of four steps those are plans, implementation, reflection, and evaluation.The data was taked through observation, field note, interview, questioner,documentation, and speaking test in every siclus. The data was analised bykualitatif and kuantitatif methods. The success of this research is based on thegood changes among teacher or students with two criteria those are process andproduct qualities.The increase of English speaking ability through English Magazine forthe VII grade students of MTs YAPI Pakem Sleman Yogyakarta was done byusing English magazine as innovative learning media. Student used Englishmagazine to look for new vocabularies then applied it in speaking after thatstudents developed the new vocabularies to be used in daily conversation. Theused of english magazine was done in teams and discussion. The evaluation wasdone also in teams. Teacher and student's positive respons was got after usingEnglish magazine as speaking English learning media. Learning speakingEnglish through English magazine is exciting for the students and it madestudents became more active in learning English. So, learning speaking Englishthrough English magazine as supporting media can increase the ability ofspeaking English for the VII grade of MTs YAPI Pakem Sleman Yogyakarta.Key words : speaking, English, English magazine